Downregulation of let-7 by Electrical Acupuncture Increases Protein Synthesis in Mice - Huang, Ying; Yu, Manshu; Kuma, Akihiro; Klein, Janet D.; Wang, Yanhua; Hassounah, Faten; Cai, Hui; Wang, Xiaonan H. (Frontiers in Physiology, 2021)
Our previous study found that acupuncture with low frequency electrical stimulation (Acu/LFES) prevents muscle atrophy by attenuation of protein degradation in mice. The current study examines the impact of Acu/LFES on protein synthesis. Method: C57/BL6 mice received Acu/LFES treatment on hindlimb for 30 minutes once. Acu/LFES points were selected by WHO Standard Acupuncture Nomenclature and electric stimulation applied using an SDZ-II Electronic acupuncture instrument. Muscle protein synthesis was measured by the surface-sensing of translation (SUnSET) assay. Exosomes were isolated using serial centrifugation and concentration and size of the collected exosomes were measured using a NanoSight instrument. The mature microRNA library in serum exosomes was validated using a High Sensitivity DNA chip. Results: Protein synthesis was enhanced in the both hindlimb and forelimb muscles. Blocking exosome secretion with GW4869 decreased the Acu/LFES-induced increases in protein synthesis. MicroRNA-deep sequencing demonstrated that four members of the Let-7 miRNA family were significantly decreased in serum exosomes. Real time qPCR further verified Acu/LFES-mediated decreases of let-7c-5p in serum exosomes and skeletal muscles. In cultured C2C12 myotubes, inhibition of let-7c not only increased protein synthesis, but also enhanced protein abundance of Igf1, Igf1 receptor. Using a luciferase reporter assay, we demonstrated that let-7 directly inhibits Igf1. Conclusion: Acu/LFES on hindlimb decreases let-7-5p leading to upregulation of the Igf1 signaling and increasing protein synthesis in both hindlimb and forelimb skeletal muscles. This provides a new understanding of how the electrical acupuncture treatment can positively influence muscle health.